The loaded weapon - MacNeil, Robert (Sydney, NSW. : BBC Education & Training, 1986)
Investigates the Irish influence on both the English and American dialects. Shows that in acquiring English as a second language, the Irish invested the tongue with certain seventeenth-century Irish characteristics
Copy available in DVD format
Title from data sheet
Backup available in VHS
Keywords: English language -- Ireland -- History; English language -- Foreign elements -- Irish -- History